5/6=-1/8x

Simple and best practice solution for 5/6=-1/8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/6=-1/8x equation:


x in (-oo:+oo)

5/6 = (-1/8)*x // - (-1/8)*x

5/6-((-1/8)*x) = 0

(1/8)*x+5/6 = 0

1/8*x+5/6 = 0 // - 5/6

1/8*x = -5/6 // : 1/8

x = -5/6/1/8

x = -20/3

x = -20/3

See similar equations:

| 1/3x2-4=21 | | 7x^2+6xy-y^2=0 | | 4(x+6)-3x=-2x+2-8 | | 0.7x-33.33=x+7 | | 11a-b+3a-(-7b)= | | w^2-3w-1890=0 | | 12x^2-(4x-3)(3x+1)=-2 | | 4(x-4)+2x=3(x-2)+5 | | 0.75x-33.3=x+7 | | U=23(6)+240 | | 3x-x=15 | | U=23n+240 | | 6x+9-7x-14=0 | | -3t(t-1)=2t+6 | | 2/2x-5/6x | | U=14n+9n+231+9 | | (8x^5)/(3)-(7x^3)/(6) | | s/616 | | -9h+15=27-2h | | 76-4x=7x-21 | | 6m-7n^5/3m^3*n^3 | | 1/3×21 | | 10x+8(x-3)-8= | | -6(x-1)-7=-7x+7 | | 10.8a+9.8a-7.9=-7.6 | | (x+6)((2x-1)(x+6))=0 | | (3b-4)(6b+5)-2= | | x=4/3×3.14×7^3 | | -14a+9=11a+12 | | 4/7=2c | | 2n+b-3n=-6 | | f(x)=(x^2-3x-1)/x |

Equations solver categories